Gender, homelessness, hospitalization and methamphetamine use fuel depression among people who inject drugs: implications for innovative prevention and care strategies - Moulis, Lionel; Le, Sao Mai; Hai, Vinh Vu; Huong, Duong Thi; Minh, Khuê Pham; Oanh, Khuat Thi Hai; Rapoud, Delphine; Quillet, Catherine; Thi, Tuyết Thanh Nham; Vallo, Roselyne; Hoang, Giang Thi; Moles, Jean-Pierre; et al. (Frontiers in Psychiatry, 2023)
Introduction The co-occurrence of substance use disorder and mental disorder, known as dual diagnosis, has a distressingly high prevalence among individuals grappling with either of these conditions. Mood disorders, especially depression, constitute a substantial burden for People Who Inject Drugs (PWID) and a significant public health concern in Vietnam. Identifying risk factors for depression in PWID is imperative for the development of targeted interventions. Methods We enrolled PWID into a cohort using the respondent-driven sampling method. Over a 36-month period, we systematically tracked the emergence of depression and employed multiple imputation in conjunction with a mixed nonlinear model to pinpoint risk factors for depression in this demographic. At inclusion, depression was screened using the PHQ-2 questionnaire, and subsequent episodes of depression were assessed semi-annually using the CES-D8. Results 391 PWID (26.6%) were depressed. Major risk factors for depression included being female, not having a permanent residency, having been hospitalized and using methamphetamine more than weekly. Other risk factors included age, being single, not having a health insurance card and not being on methadone. Limitations The exclusion of missing visits and social desirability could have led to selection and information biases. In this observational study, confusion biases are possible despite our best efforts. Conclusion Depression is alarmingly frequent in PWID. In this study taking in account the chronological relationship between sociodemographic and clinical factors and depression, risk factors were identified in this specific setting of low-to-middle income country. The findings highlight the need to develop innovative targeted psychiatric interventions with the help of supporting peers.